Tasawuf POP di Instagram: Antara Komodifikasi Agama dan Gaya Hidup Religius - Syamsul Wathoni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The purpose of this study is to analyze how the phenomenon of Pop Sufism on Instagram represents the process of commodification of religion while simultaneously forming a new construction of religious lifestyle through visual, symbolic, and narrative strategies in the digital space. This study uses a netnography method to observe the culture and behavior of Instagram users in representing Sufism through digital content, with the researcher positioned as an observer as a participant. The research object focused on two accounts, @arahbatin and @alfilosufiyah_institute, with data in the form of posts, captions, and user interactions analyzed using the theory of commodification and Islamic Lifestyle. The analysis aims to understand the paradox of pop Sufism which simultaneously opens access to Islamic spirituality and shows the process of commodification of religion in modern digital culture. This study found that pop Sufism on Instagram is the result of the transformation of culture, media, and religion in the digital era, which changes Sufism teachings from deep spiritual practices to popular knowledge in the form of quotes and aesthetic visuals. This phenomenon demonstrates the process of commodification of religion, where spiritual values ​​shift into social exchange values ​​through likes, shares, and online religious images. The two accounts, @alfilosufiyah_institute and @arahbatin, represent two faces of pop Sufism one cosmopolitan and universal, the other contextual and everyday as expressions of a modern religious lifestyle.